2022
DOI: 10.3390/life12101478
|View full text |Cite
|
Sign up to set email alerts
|

Improving Winter Wheat Photosynthesis, Nitrogen Use Efficiency, and Yield by Optimizing Nitrogen Fertilization

Abstract: Wheat is the third most producing crop in China after maize and rice. In order to enhance the nitrogen use efficiency (NUE) and grain yield of winter wheat, a two-year field experiment was conducted to investigate the effect of different nitrogen ratios and doses at various development stages of winter wheat (Triticum aestivum L.). A total of five N doses (0, N75, N150, N225, and N300 kg ha−1) as main plots and two N ratios were applied in split doses (50%:50% and 60%:40%, referring to 50% at sowing time and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
2
9
0
1
Order By: Relevance
“…The HI shows a significant positive correlation with GY in our study [75]. Our results were consistent with those of Peng et al [76], Ayadi et al [77], Kubar et al [78], Boulelouah et al [79], and Wang et al [80]. Multiple research studies have shown that it is possible to achieve high GY and NUE by focusing on the distribution of biomass into the grains rather than solely increasing its concentrations [80].…”
Section: Discussionsupporting
confidence: 92%
“…The HI shows a significant positive correlation with GY in our study [75]. Our results were consistent with those of Peng et al [76], Ayadi et al [77], Kubar et al [78], Boulelouah et al [79], and Wang et al [80]. Multiple research studies have shown that it is possible to achieve high GY and NUE by focusing on the distribution of biomass into the grains rather than solely increasing its concentrations [80].…”
Section: Discussionsupporting
confidence: 92%
“…The N levels from 75 to 150 kg N ha −1 reliably boost yields, harvest index, and N absorption. Some genotypes performed well at all N rates; Kubar et al [27] found similar findings.…”
Section: Effects Of N Fertilization On Wheat Yields Harvest Index And...mentioning
confidence: 71%
“…The two genotypes ('HD 3249' and 'HD 3117') with the greatest straw yield had N150 splits, which increased photosynthesis and dry matter output. The top dressing of wheat genotypes with the right dosage and timing of N may boost yields and HI [27][28][29][30]. The huge production discrepancies between the three N levels show that crop yields may be increased, particularly in plots with low N fertilization.…”
Section: Effects Of N Fertilization On Wheat Yields Harvest Index And...mentioning
confidence: 99%
“…Biochar moreover has an effect on crop nutrient absorption, improving plants' capacity to use available nutrients. Several studies have demonstrated that using biomass charcoal enhances soil nitrogen, phosphorus, and potassium absorption in wheat (Van et al, 2010), maize (Liu et al, 2009Kubar et al, 2022), and radish (Chan et al, 2007) within a limited range. An increasing amount of data indicates that biochar has an effect on plant development and yield Gu et al, 2018;Taghizadeh-Toosi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%